2021
DOI: 10.3390/genes12071090
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Transcriptomic and Epigenetic Profiles of Gonadal Primordial Germ Cells of White Leghorn and Green-Legged Partridgelike Chicken Embryos

Abstract: The Green-legged Partridgelike fowl is a native, dual-purpose Polish chicken. The White Leghorn has been intensively selected for several decades to mainly improve reproductive traits. Primordial germ cells (PGCs) represent the germline stem cells in chickens and are the only cells that can transfer the information stored in the genetic material from generation to generation. The aim of the study was to carry out a transcriptomic and an epigenetic comparison of the White Leghorn and Green-legged Partridgelike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…These studies mainly focused on relationship between epigenetic regulation of economic trait, such as muscle content, immunity ( David et al, 2019 ; Willems et al, 2016 ), and further studies focusing on the effect of environment to the germ cell development remains to be explored. Dunislawska et al compared epigenetic regulation of PGCs between Green-legged Patridgelike fowl ( GP ) and White Leghorn and found faster development of GP embryo compared to that of White Leghorn and suggested that epigenetic mechanism of chicken embryo development depends on genetic background, environment, and gender ( Dunislawska et al, 2021 ). Therefore, when investigating epigenetic mechanism of chicken germ cells, external factors, including breeds, environmental factors, and genders, need to be considered.…”
Section: Non-coding Rnamentioning
confidence: 99%
“…These studies mainly focused on relationship between epigenetic regulation of economic trait, such as muscle content, immunity ( David et al, 2019 ; Willems et al, 2016 ), and further studies focusing on the effect of environment to the germ cell development remains to be explored. Dunislawska et al compared epigenetic regulation of PGCs between Green-legged Patridgelike fowl ( GP ) and White Leghorn and found faster development of GP embryo compared to that of White Leghorn and suggested that epigenetic mechanism of chicken embryo development depends on genetic background, environment, and gender ( Dunislawska et al, 2021 ). Therefore, when investigating epigenetic mechanism of chicken germ cells, external factors, including breeds, environmental factors, and genders, need to be considered.…”
Section: Non-coding Rnamentioning
confidence: 99%